Evolução do gene mitocondrial COI em Aeglidae (Crustacea, Anomura) e implicações para DNA barcoding - Freitas, Thaís Kaus de (2014)
The mitochondrial gene COI is widely used as a molecular marker, and the region used for DNA barcoding is getting more and more popular to species delimitation and identification. However, the evolution patterns can vary along the genes depending on factors as the gene position in genome and taxonomic group, among others. Using one unique delimited region for all groups may not be suitable to a certain targeted taxon, or to answer its evolutionary questions. We examined the patterns of COI intra- and interspecific nucleotide divergence for aeglid crustaceans and we found highly variable divergence profiles along the COI gene; a possible evolutionary pattern for the Jerry-Pat region; lacking of evolutionary pressures by concentrated divergence; intra- and interspecific divergence levels overlap, but no overlapping in substitution profiles along the gene; a putative new COI region to access the total COI diversity in aeglids. We conclude that the barcoding region does not accurately reflect the evolution of the gene COI in aeglids.